INFLUENCE OF ORGANIZATIONAL RESTRUCTURING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE NATIONAL DEVELOPMENT UNIVERSITY (UPN) "VETERAN" EAST JAVA - Ariska Pramesti Sagita Cahyani; Arimurti Kriswibowo (DIA: Jurnal Administrasi Publik, 2022)
Public bad perception of the State Civil Apparatus (ASN) often occurs in the community, especially related to employee performance. Problems in the bureaucratic realm one of them concerns the composition of organizations that tend to grow. The more swollen the structure, it will hinder the process of public service. With the simplification of bureaucracy makes it more efficient to realize good governance. The change from structural positions in echelons III and IV that were converted into functional positions resulted in implications for work motivation. This will have an impact on the performance of the resulting employees. In this study using quantitative research methods. Data analysis techniques are applied using structural model equations (SEM) with the WarpPLS approach. Respondents were used as many as 33 employees of UPN "Veteran" East Java who were affected by the echelon cuts. The result of this study is that organizational restructuring has a weakly significant influence on employee performance with p = 0.09 and a path coefficient of 0.21. While work motivation has a strong significant influence on employee performance with p<0.01 and track coefficient of 0.75